Peran Artificial Intelligence dalam Pengembangan Metode Penelitian Pendidikan: Studi Kepustakaan atas Peluang dan Tantangan - Arina Manasikana; Dena Aulia Harani; Nikki Azyati; Nurul Azwa; Miftahir Rizqa (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
The rapid development of Artificial Intelligence (AI) has brought significant changes in various fields, including educational research. AI not only serves as a technical tool, but also has the potential to change the way researchers design, conduct, and analyze research. This study aims to map the opportunities for utilizing AI in the development of educational research methods, identify challenges and limitations, and formulate recommendations for the critical, ethical, and contextual application of AI. The method used is library research by analyzing national and international scientific journal articles relevant to the theme of AI and educational research methodology. Data were collected through documentation techniques and analyzed using content analysis to identify themes, patterns, and trends in AI utilization. The results of the study show that AI offers great opportunities to improve the efficiency and depth of research through the automation of data collection and analysis, bibliometric-based literature mapping, and support for qualitative, quantitative, and mixed-methods research designs. However, this study also found a number of serious challenges, such as algorithmic bias, the risk of data privacy violations, limitations of context and interpretation, and inequalities in access to infrastructure and technological literacy. Therefore, the integration of AI in educational research requires a clear ethical and methodological framework, increased researcher capacity, and supportive policies and infrastructure so that the use of AI can improve the quality and accountability of educational research in the digital age. Keywords: artificial intelligence, educational research methods, literature review, opportunities and challenges, research ethics